Impact Of Global Semiconductor Shortage on The Domestic New Energy Vehicle Supply Chain in Australia And Measures to Mitigate Such Risks in The Future - Li, Binghui (Transactions on Economics, Business and Management Research, 2024)
Different industries have been affected by the shortage of semiconductors globally, and one of the most affected industries is the New Energy Vehicle (NEV) industry within Australia. Semiconductors play a massive role in NEV features like battery management and power management. These factors include the COVID-19 pandemic, the rise in electronics demand, natural calamities, and most importantly the shortage which has affected NEV production and sales in Australia. This paper discusses the consequences of the lack of supply of such components on the Australian NEV supply chain: They stop production, low inventory levels, financial losses, and slowed innovation. It brings out vulnerability issues including dependence on limited suppliers from Asia and the absence of chip-making factories within North America. Based on the identified threats, the paper outlines the following solutions: supplier diversification, increasing inventory levels, raising supply chain visibility, investing in domestic semiconductor production, incentives for buyers, and sourcing non-semiconductor material technologies. Such measures are strategic and intended to secure an NEV supply chain in Australia that is both sustainable and environmentally friendly.